2021
DOI: 10.21037/tlcr-21-32
|View full text |Cite
|
Sign up to set email alerts
|

Earlier extracranial progression and shorter survival in ALK- rearranged lung cancer with positive liquid rebiopsies

Abstract: Background: Liquid rebiopsies can detect resistance mutations to guide therapy of anaplastic lymphoma kinase-rearranged (ALK + ) non-small-cell lung cancer (NSCLC) failing tyrosine kinase inhibitors (TKI).Here, we analyze how their results relate to the anatomical pattern of disease progression and patient outcome.Methods: Clinical, molecular, and radiologic characteristics of consecutive TKI-treated ALK + NSCLC patients were analyzed using prospectively collected plasma samples and the 17-gene targeted AVENIO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…In our study population, VAF mean > 0 at therapy baseline predicted shorter therapy duration compared to cases without detected variants (VAF mean = 0). This parallels findings demonstrating that ctDNA at baseline indicates poor prognosis in various cancers 18 , 27 , 45 – 47 . Pretreatment VAF levels have also been shown to be prognostic of treatment response with immune checkpoint inhibitors in patients with advanced solid tumors 31 , 48 .…”
Section: Discussionsupporting
confidence: 86%
“…In our study population, VAF mean > 0 at therapy baseline predicted shorter therapy duration compared to cases without detected variants (VAF mean = 0). This parallels findings demonstrating that ctDNA at baseline indicates poor prognosis in various cancers 18 , 27 , 45 – 47 . Pretreatment VAF levels have also been shown to be prognostic of treatment response with immune checkpoint inhibitors in patients with advanced solid tumors 31 , 48 .…”
Section: Discussionsupporting
confidence: 86%
“…Several studies reported a compound mutations rate of ∼30%-35% on treatment with multiple lines of ALK TKI. 28 , 29 Here, we identified three compound mutations, ALK D1203N/L1196M, ALK G1202R/L1196M, and ALK G1202R/F1174C, after patients progressed on later-line lorlatinib. G1202R-based compound mutations including ALK G1202R/L1196M, ALK G1202R/F1174C, ALK G1202R/l1198F, ALK G1202R/G1269A have been shown to be potentially lorlatinib resistant through steric hindrances in the ALK kinase domain.…”
Section: Discussionmentioning
confidence: 91%
“…In this context and considering that in lung cancer the tumor is often difficult to reach and may need an invasive and potentially harmful procedure, the continuing development of the analyses of liquid biopsies can noninvasively detect any targetable genomic alteration and guide corresponding targeted therapy. Moreover, liquid biopsy might help in monitoring the response to treatment and exploring the genetic changes at resistance, overcoming spatial and temporal heterogeneity [43,44].…”
Section: Discussionmentioning
confidence: 99%